A randomised, double-blind, sham-controlled study of granulocyte/monocyte apheresis for moderate to severe Crohn's disease. Issue 9 (3rd July 2012) - Sands, Bruce E; Katz, Seymour; Wolf, Douglas C; Feagan, Brian G; Wang, Tao; Gustofson, Lisa-Marie; Wong, Cindy; Vandervoort, Margaret K; Hanauer, Stephen
Abstract : Objectives: Activated granulocytes and monocytes may contribute to the pathogenesis of Crohn's disease (CD). In small, uncontrolled studies, granulocyte/monocyte apheresis (GMA) has shown promise in treating CD. We conducted a randomised, double-blind study to compare GMA with a sham procedure in patients with moderate to severe CD. Design: Patients with active CD as defined by a Crohn's Disease Activity Index (CDAI) of 220–450 were randomly allocated in a 2:1 ratio to treatment with GMA using the Adacolumn Apheresis System (JIMRO, Takasaki, Japan) or sham apheresis. Ten apheresis sessions were scheduled over a 9-week period, and efficacy was evaluated at week 12. The primary end point was the proportion of patients achieving clinical remission (CDAI score ≤150 without use of prohibited drugs). Results: Clinical remission was achieved by 17.8% of patients in the GMA group (n=157) compared with 19.2% of those in the sham control group (n=78) (absolute difference −1.4% (95% CI−12.8% to 8.5%), p=0.858). Clinical response (defined as a ≥100-point decrease in CDAI) was achieved by 28.0% and 26.9% of patients in the GMA and sham groups, respectively (p=1.000). The two treatments produced similar changes from baseline in CDAI and quality of life, as well as in disease severity assessed endoscopically. The incidence and types of adverse events did not differ between groups. Conclusions: GMA was well tolerated, but this study did not demonstrate its effectiveness over a sham procedure in inducing clinical remission or response in patients with moderate to severe CD. Clinical trial registration number: Clinical Trials.gov identifier NCT00162942 .